Defective carbon-based materials: controllable synthesis and electrochemical applications. Issue 5 (September 2021) - Wu, Qilong; Yan, Xuecheng; Jia, Yi; Yao, Xiangdong
Highlights: An overview about recent progress of defect electrocatalysis. A discussion of controllable synthetic methodology for DCMs. Emphasis on theoretical guidance in designing complex carbon defect structures. Perspective about operando characterizations in exploring "dynamic" active centers. Summarize the key challenges and future opportunities in this field. Abstract: Defective carbon-based materials (DCMs) have recently been considered as one of the most promising alternatives to precious metal electrocatalysts owing to their irreplaceable advantages, such as environmentally friendly, low cost and high structural tunability. Despite remarkable progress has been achieved, grand challenges of their further development are still remained by the traditional "trial-and-error" approaches, mainly due to the lack of precise synthetic methodologies as well as in-depth understandings of active centers and underlying electrocatalytic mechanisms. Herein, this review will provide a comprehensive overview and perspective on the critical issues and possible solutions regarding the controllable synthesis of DCMs, with special emphasis on the theoretical guidance in designing complex carbon defect structures and operando characterizations in exploring "dynamic" active centers. More importantly, it will also highlight recent advances in the applications of DCMs for the cutting-edge "E-Refinery", focusing on the electrochemical conversion of electricity into fuels and chemical building blocks (e.g., H2, O2, CH4, C2 H4, CH3 OH, C2 H5 OH, NH3 and other organic compounds). Finally, further challenges and opportunities are summarized to shed some light on the unexploited area and future directions in expectation of stimulating the broad interest of interdisciplinary researchers. Graphical abstract: Image, graphical abstract